Potential of mixed consortium of Enterobacteriaceae and Serratia marcescens in synthetic wastewater treatment and power generation in microbial fuel cell - Leung, Dexter Hoi Long (2020)
Microbial Fuel Cell (MFC) is a promising technology that can treat wastewater and generate electricity simultaneously. Basic principle of an MFC uses microorganism in the form of biofilm that is cultivated on surface of anode that oxidizes the substrate provided. Common challenge faced for the realization of this technology in actual wastewater treating system includes the strict control of specific microbial strain growth throughout the treatment period. To overcome this, the performance of using common water-borne bacteria as the extracellular electron transfer (EET) strain was evaluated. A total of 14 water-borne bacteria, mostly from Enterobacteriaceae family, were isolated and subsequently identified from two different water sources, one with a more diverse community in an open system (lake) while the other is a more controlled environment in a closed system (household aquarium). Two dual-chambered MFC were set-up with different anode materials made up of graphite plate and carbon cloth to study the growth of a mixed consortium of bacteria isolated from lake water and pure culture from aquarium on respective electrode surface. Glucose, lactate, acetate, fumarate, and lastly fumarate coupled with lactate were then supplied as synthetic wastewater to determine power generation and wastewater treating ability. Pure culture of Serratia marcescens isolated from household aquarium were then used in similar set-up to evaluate their effect on MFC. The power densities generated from two reactors with different anode materials showed that the mixture of waterborne bacteria demonstrated better growth on graphite plate compared with carbon cloth. All reactors were capable in generating low amount of electricity, with highest at 0.90 mW/m2 through using fumarate coupled with lactate, lowest for all reactors when using glucose. This is due to the position of glucose in the respiratory pathway as compared to acetate. Additionally, MFC was able to utilise substrate inoculated efficiently, with high Chemical Oxygen Demand (COD) removal recorded at 95% when fumarate was supplied with lactate. However, low Coulombic Efficiency (CE) value was obtained which suggests electron loss during the EET process to other respiratory process or pathways such as methanogenesis. While it can generate power and treat synthetic wastewater, efforts such as characterisation, and engineering from the genetic aspects were still needed for these organisms to be applied in an MFC.